Dinámicas familiares en tiempo de pandemia por Covid 19 en Cartago (2022)
The purpose of this research work is to describe the functioning of family dynamics in couples of parents of a private garden in times of pandemic by Covid 19 in the city of Cartago, which was developed from a qualitative methodology, to through a descriptive scope, for which the development of a semi-structured interview was proposed as an instrument for collecting information.